A nationwide survey of Italian Centers for Cognitive Disorders and Dementia on the provision of care for international migrants. (10th March 2022) - Canevelli, Marco; Cova, Ilaria; Remoli, Giulia; Bacigalupo, Ilaria; Salvi, Emanuela; Maestri, Giorgia; Nicotra, Alessia; Valletta, Martina; Ancidoni, Antonio; Sciancalepore, Francesco; Cascini, Silvia; Bargagli, Anna Maria; et al.
Abstract: Background: More than 500, 000 dementia cases can be estimated among migrants living in Europe. There is the need to collect "real world" data on the preparedness of healthcare services to support the inclusion of migrants in the public health response to dementia. The present study aimed (i) to estimate the number of migrants referred to Italian memory clinics (Centers for Cognitive Disorders and Dementia [CCDDs]) and (ii) to identify possible barriers and resources for the provision of diversity‐sensitive care. Methods: A survey of all Italian CCDDs was conducted between December 2020 and April 2021. An online questionnaire was developed to obtain information on the number of migrants referred to Italian CCDDs in 2019, the challenges encountered in the diagnostic approach, and possible facilitators in the provision of care. Results: Overall, 343 of the 570 contacted CCDDs completed the survey questionnaire (response rate: 60.2%). Nearly 4527 migrants were referred to these services in 2019. Migrants accounted for a median 1.1% (IQR: 0.9%–2.8%) of overall CCDD referrals. More than one‐third of respondents reported that the number of migrants referred to their facilities had increased in the last 5 years. The overall quality of the migrants' cognitive assessment was deemed to be very poor or insufficient in most cases. A minority of CCDDs had translated information material on dementia and reported the possibility to contact cultural mediators and interpreters. Conclusions: A relevant number of migrants are being referred to Italian CCDDs that are still not adequately prepared to deliver diversity‐sensitive care and support. Abstract : Based on a nationwide survey of 343 Italian memory clinics (Centers for Cognitive Disorders and Dementia [CCDDs]), a relevant number of migrants are being referred to these services due to cognitive disorders. CCDDs do not seem adequately prepared to deliver diversity‐sensitive care and support. There is the need to develop and disseminate cross‐cultural cognitive assessment tools, clarify the role and activity of interpreters and cultural mediators, and train healthcare professionals in how to provide culturally competent care. Migrants (as other vulnerable groups) must be included in the public health response to dementia.